Recruitment Challenges in Mother–Infant Research: Factors Associated With Low Enrollment and Inclusion in the Synbio‐Breast Study. - Simons, Sandra; van Goudoever, Hans; Vlieg-Boerstra, Berber; Banerjee, Baisakhi (BioMed Research International, 2026)
Background: An optimal early‐life environment is crucial for child health, with human milk and the infant microbiome playing central roles. The Synbio‐Breast study investigates how maternal diet contributes to the synbiotic composition of human milk in atopic women. Despite increasing societal interest in this topic, recruitment proved challenging. Objective: The aim of this study is to quantify and analyze factors associated with low enrollment and inclusion rates and to explore strategies for improving recruitment in future mother–infant studies. Methods: Enrollment and inclusion rates and temporal trends were assessed using linear regression models, whereas associations between facilitating factors—including involvement of the PhD student, recruitment strategy, lactation meetings, and attendance at the Nine Months Fair—and enrollment were assessed using logistic regression models. Results: Of the 681 women screened, 215 expressed willingness to participate. Despite multiple efforts and adaptations to enhance engagement, enrollment remained low. After adjusting for the COVID‐19 period, only recruitment conducted by the PhD student via email—without personal contact through a healthcare professional—was significantly associated with lower odds of enrollment. Of the 215 enrolled participants, 75 were ultimately included (11% of all screened women). Key reasons for exclusion were partial breastfeeding (30.0%), antibiotic use (22.1%), and loss of interest (19.3%). Conclusion: Strict inclusion and exclusion criteria contributed to substantial low enrollment and inclusion rates in the Synbio‐Breast study. Successful recruitment in mother–infant research requires more than logistical organization; it depends on personalized engagement built on existing relationships of trust. Moreover, studies that offer no direct health benefit to participants—such as the Synbio‐Breast study—tend to have inherently lower uptake, underscoring the need for tailored and relationship‐based recruitment strategies.